Hadis dan Pergeseran Otoritas Keagamaan: Transmisi, Resepsi, dan Peran Pesantren di Era Kontemporer - Mala, Faiqotul (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
Changing times have influenced the patterns of transmission, authority, and reception of hadith within Muslim societies. This article examines the dynamics of contemporary hadith studies, emphasizing the role of Islamic boarding schools (pesantren) as traditional institutions that maintain the sanad (chain of transmission), authority, and methodology of hadith criticism. Three main findings emerge. First, the transformation of the method of hadith transmission: from the established patterns of talaqqī, ijazah, and sanad in pesantren to new forms beyond the control of scholarly authority, thus posing challenges to the authentication of riwayyah (reportage). Second, the emergence of widespread community participation in quoting, interpreting, and disseminating hadith instantly without the methodology of ‘ulūm al-ḥadīṡ, which has the potential to distort understanding. Third, the contestation of authority: pesantren function as guardians of the sanad and critique of the matan (translation), but at the same time face challenges from non-traditional figures who gain religious legitimacy through social popularity, not scholarly authority. This study confirms that Islamic boarding schools (pesantren) have a strategic position in maintaining the authenticity of hadith by integrating classical methodologies—sanad and matan criticism—and contextual responses to contemporary needs. Theoretically, this research enriches the discourse on hadith studies by highlighting the relationship between authenticity, social reception, and the institutional role of Islamic boarding schools. Practically, this article contributes to educators, researchers, and preachers in formulating hadith teaching strategies that are authentic, critical, and relevant to contemporary challenges